3D-Frameworks and 2D-networks of lanthanide coordination polymers with 3-pyridylpyrazole: photophysical and magnetic properties. Issue 38 (13th September 2022) - Youssef, Heba; Schäfer, Thomas; Becker, Jonathan; Sedykh, Alexander E.; Basso, Leonardo; Pietzonka, Clemens; Taydakov, Ilya V.; Kraus, Florian; Müller-Buschbaum, Klaus
Abstract : Reactions of anhydrous lanthanide chlorides with 3-(3-pyridyl)pyrazole result in fifteen 3D- and 2D-coordination polymers besides salt-like complexes that differ in constitution and structural extension and show versatile photophysical, thermal, and magnetic properties. Abstract : A series of 15 lanthanide-containing coordination polymers, both 3D- and 2D-networks, as well as complexes of Ln-trichlorides with 3-(3-pyridyl)pyrazole (3-PyPzH), were synthesized. A large structural diversity is observed depending on the ligand content: 3∞[Ln(3-PyPzH)Cl3 ], Ln = Eu and Gd, of sra topology, 2∞[Sm(3-PyPzH)Cl3 ], 2∞[Ln2 (3-PyPzH)3 Cl6 ]·2solv, Ln = Eu 3+, Tb 3+, Dy 3+, Ho 3+ and Er 3+, solv = Tol and MeCN, of sql topology and 2∞[Ln(3-PyPzH2 )Cl4 ], Ln = La and Nd, of hcb topology with salt like complexes of the formula [(3-PyPzH2 )][Ln(3-PyPzH)2 Cl4 ], Ln = Eu, Tb, Dy and Ho. The products were characterized by single-crystal and powder X-ray diffraction, high-temperature X-ray diffraction, differential thermal analysis and thermogravimetry (DTA/TG) combined with mass spectrometry, differential scanning calorimetry (DSC), IR-spectroscopy, UV–visible spectrophotometry, photoluminescence spectroscopy, and magnetic susceptibility. Absorption spectroscopy shows ion-specific 4f–4f transitions that can be assigned to Sm 3+, Eu 3+, Dy 3+, Ho 3+ and Er 3+ in a wide range from the UV-VIS to NIR region. An excellent antenna effect through ligand–metal energy transfer was observed in 2∞[Tb2 (3-PyPzH)3 Cl6 ]·2solv, leading to high efficiency of the luminescence indicated by a quantum yield up to 76%. Direct current magnetic susceptibility studies reveal the absence of interatomic interaction for Dy 3+ and Er 3+ and weak ferromagnetic interaction for Ho 3+ . Thermal analysis shows good stability up to 365 °C for 2∞[Ho2 (3-PyPzH)3 Cl6 ]·2MeCN.